Bradykinin signaling regulates solute permeability and cellular junction organization in lymphatic endothelial cells. (9th October 2019) - Kempe, Sybille; Fois, Giorgio; Brunner, Cornelia; Hoffmann, Thomas K.; Hahn, Janina; Greve, Jens
Abstract: Objective: Determine the effect of bradykinin on solute permeability and cellular junctional proteins in human dermis microvascular endothelial cells. Methods: Cells were characterized by immunofluorescence and fluorescence‐activated cell sorting. Macromolecular transport of dextran and albumin was monitored. Junctional protein expression and phosphorylation were determined by immunoblot analyses. Intracellular calcium and cAMP levels were evaluated. Target gene expression at mRNA and protein levels was determined. Results: Human dermis microvascular endothelial cells comprised 97% lymphatic endothelial cells. Bradykinin increased the permeability to dextran in a concentration‐dependent manner, while reduced the permeability to albumin. Bradykinin treatment down‐regulated VE‐cadherin expression and affected its phosphorylation status at Tyr731. It also down‐regulated claudin‐5 expression at the transcriptional level through bradykinin‐2‐receptor signaling. An increase in the intracellular calcium levels and a reduction in the cAMP concentration were associated effects. Finally, bradykinin induced the up‐regulation of vascular endothelial growth factor‐C protein which was found increased in BK‐induced human dermis microvascular endothelial cells culture supernates. Conclusions: Human dermis microvascular endothelial cells represent a model of lymphatic endothelial cells, in which bradykinin‐2‐receptor is expressed. Bradykinin‐induced bradykinin‐2‐receptor signaling through intracellular calcium mobilization and reduction in cAMP levels, triggered changes in solute permeability and cellular junction expression. It further up‐regulated vascular endothelial growth factors‐C protein expression, which is a key modulator of lymphatic vessels function and lymphangiogenesis.